Analisis Reaksi Pasar Terhadap Keterlambatan Penyampaian Laporan Keuangan Interim - Vionny Tirza; Tri Joko Prasetyo (Departement of Mathematics Education, 2024)
The late submission of interim financial reports causes companies listed on the Indonesia Stock Exchange (IDX) to pay a fairly large amount of fines. The Financial Services Authority (OJK) issued regulations for companies going public to report and publish audited annual financial reports, so that each company must submit accordingly and on time. Therefore, this research aims to determine the comparison of abnormal returns and stock trading volume before and when there is a delay in submitting financial reports. The data used in this research are the financial reports of companies registered on the IDX that are late in submitting financial reports. The results of this research show significant differences in abnormal returns and stock trading volume before and after the delay in submitting interim financial reports. The study uses the average difference test method, with the object of the financial statements of 35 listed companies that have not submitted financial reports for the period 2021 to 2022. After descriptive statistical analysis, there are company values that are recorded as poor in submitting their interim financial reporting. The results showed that there was a significant difference between the performance before and after the company's financial reporting on abnormal returns and stock trading volume on the submission of financial reports.